Yellow Fever 17DD Vaccine Virus Infection Causes Detectable Changes in Chicken Embryos. - Pedro Paulo de Abreu Manso; Barbara C E P Dias de Oliveira; Patrícia Carvalho de Sequeira; Yuli Rodrigues Maia de Souza; Jessica Maria dos Santos Ferro; Igor José da Silva; Luzia Fátima Gonçalves Caputo; Priscila Tavares Guedes; Alexandre Araujo Cunha dos Santos; Marcos da Silva Freire; Myrna Cristina Bonaldo; Marcelo Pelajo-Machado (Public Library of Science (PLoS), 2015)
The yellow fever (YF) 17D vaccine is one of the most effective human vaccines ever created. The YF vaccine has been produced since 1937 in embryonated chicken eggs inoculated with the YF 17D virus. Yet, little information is available about the infection mechanism of YF 17DD virus in this biological model. To better understand this mechanism, we infected embryos of Gallus gallus domesticus and analyzed their histopathology after 72 hours of YF infection. Some embryos showed few apoptotic bodies in infected tissues, suggesting mild focal infection processes. Confocal and super-resolution microscopic analysis allowed us to identify as targets of viral infection: skeletal muscle cells, cardiomyocytes, nervous system cells, renal tubular epithelium, lung parenchyma, and fibroblasts associated with connective tissue in the perichondrium and dermis. The virus replication was heaviest in muscle tissues. In all of these specimens, RT-PCR methods confirmed the presence of replicative intermediate and genomic YF RNA. This clearer characterization of cell targets in chicken embryos paves the way for future development of a new YF vaccine based on a new cell culture system.